Carbon storage in tree biomass dispersed in pastures in the arid Caribbean region of Colombia - LOMBO, Darwin F.; BURBANO, Esteban; ARIAS, Jaime A.; RIVERA, Milton (Forest Systems, 2023)
Aim of study: To determine the importance in terms of carbon sequestration of dispersed trees in pasture lands as a greenhouse gas (GHG) mitigation measure. Area of study: The study was carried out in the municipality of Agustin Codazzi (Cesar Department, Colombia), between October 2020 and March 2021. Material and methods: We characterized 43.57 hectares dispersed amongst sixteen plots and all trees with a diameter at breast height > 10 cm were measured. Allometric equations were used to estimate aboveground biomass storage and species were classified in terms of use: timber products (TP) and non-timber products (NTP). Main results: A total of 750 trees were registered, 10 families and 28 species, of which NTP and TP represented 60.71% and 32.1% respectively. Aboveground carbon stock in trees in pastures was estimated at 7.15 + 4.8 Mg C ha-1. The most abundant species were Guazuma ulmifolia Lam. and Albizia saman (Jacq.) Merr. Research highlights: NTP species present a high potential for carbon storage and provide livestock assets. Placing value on carbon storage in rangelands can offset the low opportunity cost of trees in pastures by providing incentives for carbon storage, conservation, and recovery of threatened species.